2005
DOI: 10.1089/ham.2005.6.14
|View full text |Cite
|
Sign up to set email alerts
|

Going High with Type 1 Diabetes

Abstract: This review aims to identify the main issues facing a healthy and well-controlled type-1 diabetic mountaineer at high altitude. Most of the problems are self-managed by the diabetic climber although the risk of serious morbidity or even death remains. Given the scarce evidence on diabetes at altitude, an extensive search of the literature, including case reports and anecdotes was carried out to reach the recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…We have found a total of eight reported or cited cases of diabetic ketoacidosis at altitude, three of which were lethal (65), and one occurred in a subject with undiagnosed type 2 diabetes and HAPE (66). One fatal case of HACE in a subject with type 1 diabetes was reported (67), and one case of AMS in a subject with metabolic syndrome was reported (68). Type 2 diabetes is associated with obesity and a lower ventilatory response to hypoxia (6), both of which are risk factors for the development of AMS (69,70).…”
Section: Acute Mountain Illnesses In Subjects With Diabetesmentioning
confidence: 99%
“…We have found a total of eight reported or cited cases of diabetic ketoacidosis at altitude, three of which were lethal (65), and one occurred in a subject with undiagnosed type 2 diabetes and HAPE (66). One fatal case of HACE in a subject with type 1 diabetes was reported (67), and one case of AMS in a subject with metabolic syndrome was reported (68). Type 2 diabetes is associated with obesity and a lower ventilatory response to hypoxia (6), both of which are risk factors for the development of AMS (69,70).…”
Section: Acute Mountain Illnesses In Subjects With Diabetesmentioning
confidence: 99%
“…On the other hand, the current study has clearly shown that HbA1c levels significantly increased in diabetic subjects living in moderate altitude compared to diabetic individuals living at sea level. It has been demonstrated that diabetic mountaineers report a reduction in metabolic control (Pavan et al, 2003;Leal, 2005), as demonstrated by elevated HbA1c, insulin requirements, and capillary blood glucose (Moore et al, 2001;Pavan et al, 2004). Reduced insulin sensitivity is thought to be the major factor contributing to these effects (Brubaker 2005;Leal 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that diabetic mountaineers report a reduction in metabolic control (Pavan et al, 2003;Leal, 2005), as demonstrated by elevated HbA1c, insulin requirements, and capillary blood glucose (Moore et al, 2001;Pavan et al, 2004). Reduced insulin sensitivity is thought to be the major factor contributing to these effects (Brubaker 2005;Leal 2005). It was recently suggested that the influence of hypoxia is associated with high glucose (Kanafi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a wilderness setting, ketoacidosis carries a high risk of mortality (Basnyat,1995;Shlim and Gallie, 1992). It would appear that it is a relative lack of insulin (reduced or no dosing, reduced efficacy from environmental/heat damage, misdosing due to meter error) in conjunction with other factors such as dehydration, infection, AMS, or continuing to exercise with ketonuria that particularly raises risk (Leal, 2005;Moore et al, 2001b).…”
Section: Hyperglycemia and Ketoacidosismentioning
confidence: 99%